Pengaruh Kecerdasan Spiritual dan Penerapan Etos Kerja Islam Terhadap Kinerja Karyawan (Studi Kasus pada Distributor Busana Muslimah Madina Collection). - Fenda, Madjida Ayu; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study aims to examine the effect of spiritual intelligence and the application of Islamic work ethic to the performance of Madina Collection Muslim Clothing Distributor employees. This research was conducted using a quantitative approach. The number of samples used as many as 36 respondents, taken from all employees who worked at the Madina Collection Muslim Clothing Distributor using saturated sample techniques. This study uses a questionnaire that was measured using a Likert Scale and analyzed using SPSS 20. Based on the T test and the F test that has been done shows that the variable spitual intelligence and Islamic work ethic variables partially and simultaneously, have a significant effect on the performance variable. The test based on the coefficient of determination R2 shows that the variables of spiritual intelligence and Islamic work ethic variables have an influence of 85.7% on the performance variable.